Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can I find a laurent series for $\sin z \sin(1/z)$ for $z \neq 0$?

Is it possible to multiply two laurent series? I saw that in wikipedia, it's not generally possible.

share|cite|improve this question
But $z \mapsto \sin z$ is analytic, and this is a very special case of multiplication. – Siminore Sep 14 '12 at 9:33
Isn't the singularity at $z=0$ an essential one? – Hagen von Eitzen Sep 14 '12 at 9:33
I don't know if you know Gauchy-product, if not have a look: – Lucien Sep 14 '12 at 9:38
@HagenvonEitzen Yes, it is. For a pole, the number of terms of the Laurent series with negative exponent is finite. Here is will be infinite. – Sasha Sep 14 '12 at 12:15
up vote 3 down vote accepted

Operate formally. Fix finite $z\not=0$. Then each expand each sine into Taylor series: $$\begin{eqnarray} \sin(z) \sin\left(\frac{1}{z}\right) &=& \sum_{n=0}^\infty (-1)^n \frac{z^{2n+1}}{(2n+1)!} \sum_{m=0}^\infty (-1)^n \frac{z^{-2m-1}}{(2m+1)!} \\ &=& \sum_{n=0}^\infty \sum_{m=0}^\infty \frac{(-z^2)^{n-m}}{(2n+1)!(2m+1)!} = \Big| \text{insert identity}\Big| \\ &=& \sum_{k=-\infty}^\infty \sum_{n=0}^\infty \sum_{m=0}^\infty \frac{(-z^2)^{n-m}}{(2n+1)!(2m+1)!} \delta_{k,n-m} \\ &=& \sum_{k=-\infty}^\infty (-z^2)^k \sum_{m=\max(0,-k)}^\infty \frac{1}{(2(k+m)+1)!(2m+1)!} \\ &=& \sum_{k=-\infty}^\infty (-z^2)^k \sum_{m=0}^\infty \frac{1}{(2m+2 |k| +1)!(2m+1)!} \end{eqnarray} $$ The latter sum can be evaluated in terms of Bessel functions, giving: $$ \sin(z) \sin\left(\frac{1}{z}\right) = \frac{1}{2} \sum_{k=-\infty}^\infty (-z^2)^k \left(I_{2|k|}(2)- J_{2|k|}(2)\right) $$ Indeed: $$\begin{eqnarray} \sum_{m=0}^\infty \frac{1}{(2m+2 |k| +1)!(2m+1)!} &=& \sum_{m=0}^\infty \frac{1+(-1)^m}{2} \frac{1}{(m+2 |k| +1)!(m+1)!} \\ &=& \sum_{m=0}^\infty \frac{1-(-1)^m}{2} \frac{1}{(m+2 |k|)!(m)!} \\ &=& \frac{1}{2} I_{2|k|}(2) - \frac{1}{2} J_{2|k|}(2) \end{eqnarray} $$

share|cite|improve this answer
And notice that all the sums converge absolutely, so there is no issue with justifying the formal manipulations. – David Speyer Sep 14 '12 at 13:56
@DavidSpeyer Can I get more details? Why is it possible that all the rearrangements and multiplications? – Gobi Sep 14 '12 at 15:34

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.